Laetisaria fuciformis (Basidiomycota, Corticiaceae), nuevo registro de un parásito fúngico sobre gramíneas en el sur de Chile Laetisaria fuciformis (Basidiomycota, Corticiaceae), new record of a fungal grass parasite from southern Chile - Götz Palfner (Universidad de Concepción, 2010)
A new record of the fungal grass parasite Laetisaria fuciformis from southern Chile is described and its biology is briefly discussed.